1971
DOI: 10.1017/s0043174500050712
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Phytotoxicity and Root Uptake of Several Herbicides

Abstract: The phytotoxicity of 3-(3,4-dichlorophenyl)-1-methoxy-1-methylurea (linuron) to corn (Zea maysL.) and soybean (Glycine max(L.) Merr.) seedlings and 2-chloro-4-(ethylamino)-6-(isopropylamino)-s-triazine (atrazine) to soybean seedlings increased with increasing temperature from 20 to 30 C. The phytotoxicity of α,α,α-trifluoro-2,6-dinitro-N,N-dipropyl-p-toluidine (trifluralin) did not change significantly between 20 and 30 C. Corn and soybean plants grown at 30 C translocated more14C from14C-atrazine and soybeans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Differences in the tolerance of plant species to atrazine have been ascribed to variation in the rates of absorption and translocation of the herbicide (Vostral, Buchholtz & Kust, 1970), dissimilarity in metabolic degradation rates (Penner, 1971), and discrepancies in the ability of atrazine molecules to inhibit photosynthetic electron transport (Fuerst & Norman, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the tolerance of plant species to atrazine have been ascribed to variation in the rates of absorption and translocation of the herbicide (Vostral, Buchholtz & Kust, 1970), dissimilarity in metabolic degradation rates (Penner, 1971), and discrepancies in the ability of atrazine molecules to inhibit photosynthetic electron transport (Fuerst & Norman, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Merr.) roots increased as temperature increased from 20 to 25 °C . Similarly, oat ( Avena sativa L.) and cotton ( Gossypium hirsutum L.) leaf tissues accumulated more than twice the concentration of simazine when plants were grown at 37 °C rather than at 26 °C .…”
Section: Resultsmentioning
confidence: 99%
“…Greater herbicide absorption and translocation detected at high temperature could strengthen herbicidal effects in meristematic regions, resulting in greater phytotoxicity on grasses. Greater phytotoxicity of atrazine and simazine at higher temperatures on account of increased herbicide uptake was reported . 14 C‐atrazine uptake by soybean ( Glycine max L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in temperature has been reported to enhance phytotoxicity of sime-tryn1,2,8,15,18) simazine21), atrazine10,19,22,23), propazine3), and turbutryn3,4,5); it may stimulate the acceleration of absorption and translocation of these herbicides in the phytotoxic process3, 19,21,23). KOBAYASHI et al 9) demonstrated similar growth retardation by simetryn in pot experiments under a temperature as high as that observed in fields (32C), and found that the rate of absorption by rice roots doubled as compared with that at 27C.…”
Section: Effectmentioning
confidence: 99%